Ethnography : step-by-step - Fetterman, David M. (Applied social research methods series, 2010)
The Third Edition of the best-selling Ethnography: Step-By-Step guides readers in managing mountains of ethnographic data and making meaningful statements based on that data. The second edition provided coverage of a then "new frontier"-the Internet. This new edition builds on that coverage and offers an up-to-date discussion of technology in ethnography, covering a range of topics from technological tools to research with virtual communities. Other notable additions to this updated classic include increased coverage of ethics in ethnography and updated examples and references from a broader range of fields, so as to represent the landscape of ethnography today. Popular with readers for its friendly and accessible approach, this new edition will be an indispensable resource for doing ethnographic research. It is especially well suited for courses in ethnography, qualitative research methods, and social research methods.